2019
DOI: 10.3390/ma12152424
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of UV Irradiation on the Chemical Structure, Mechanical and Self-Healing Properties of Asphalt Mixture

Abstract: Although huge numbers of investigations have been conducted for the ultraviolet (UV) aging of asphalt binder, research rarely focuses on the asphalt mixture. In order to evaluate the aging effect of UV radiation on the asphalt mixture, a dense grade of asphalt mixture was designated and aged by UV radiation for 7, 14 and 28 days respectively. After that, the chemical functional groups of asphalt binder were tested by Fourier transform infrared spectrometer (FTIR). The semi-circular bending strength and fatigue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…Fresh bitumen had no peaks of the carbonyl group. Likewise, in Figure 9b, the sulfoxide group can be observed in the FTIR spectra, occurring due to thermo-oxidative aging during the production and storage of bitumen [44]. Figure 9b demonstrates that bitumen 1 and the PAV bitumen had a similar tendency in the sulfoxide zone.…”
Section: Effect On the Chemical Properties Of Bitumen Samples From Mo...mentioning
confidence: 78%
See 1 more Smart Citation
“…Fresh bitumen had no peaks of the carbonyl group. Likewise, in Figure 9b, the sulfoxide group can be observed in the FTIR spectra, occurring due to thermo-oxidative aging during the production and storage of bitumen [44]. Figure 9b demonstrates that bitumen 1 and the PAV bitumen had a similar tendency in the sulfoxide zone.…”
Section: Effect On the Chemical Properties Of Bitumen Samples From Mo...mentioning
confidence: 78%
“…The changes caused by aging can be found between 2000 and 600 cm −1 . These wavenumbers correspond to functional groups related to the oxidation process [44]. The peaks of the carbonyl and sulfoxide groups can be found at wavenumbers 1700 and 1030 cm −1 , respectively [44].…”
Section: Chemical Properties Of Bitumen By Ftir Testsmentioning
confidence: 98%
“…These observations showed that a layer of chitosan film was coated on the fibers' surface of chitosan treated BPFs, indicating that chitosan was chemically cross-linked on the fibers' surface. 21,22 This is mainly because the smaller molecular weight of the chitosan molecules not only deposited on the grooves and gaps on fibers' surfaces, but also entered the loose area of BPFs and reacted with carboxyl group to cross-linking.…”
Section: Acid Ph Value Effectsmentioning
confidence: 99%
“…They concluded that rejuvenators can soften aged pavement materials and consequently recover the road performance. Furthermore, self-healing characteristics of pavement materials were reported by Wu et al [13], Li et al [14], and Cai et al [15]. Wu et al [13] found that UV irradiation will weaken the macro-structure and lower the failure strength and healing index.…”
mentioning
confidence: 95%
“…Furthermore, self-healing characteristics of pavement materials were reported by Wu et al [13], Li et al [14], and Cai et al [15]. Wu et al [13] found that UV irradiation will weaken the macro-structure and lower the failure strength and healing index. Li et al [14] designed steel fiber modified asphalt concrete to promote the induction heating technology, while Cai et al [15] used engineered cementitious composites mortar to prepare flexible pavement materials with certain healing property.…”
mentioning
confidence: 95%